Regulation of Immune Cells by Eicosanoid Receptors - Nancy D. Kim; Andrew D. Luster (The Scientific World Journal, 2007)
Eicosanoids are potent, bioactive, lipid mediators that regulate important components of the immune response, including defense against infection, ischemia, and injury, as well as instigating and perpetuating autoimmune and inflammatory conditions. Although these lipids have numerous effects on diverse cell types and organs, a greater understanding of their specific effects on key players of the immune system has been gained in recent years through the characterization of individual eicosanoid receptors, the identification and development of specific receptor agonists and inhibitors, and the generation of mice genetically deficient in various eicosanoid receptors. In this review, we will focus on the receptors for prostaglandin D2, DP1 and DP2/CRTH2; the receptors for leukotriene B4, BLT1 and BLT2; and the receptors for the cysteinyl leukotrienes, CysLT1 and CysLT2, by examining their specific effects on leukocyte subpopulations, and how they may act in concert towards the development of immune and inflammatory responses.